2012
DOI: 10.15376/biores.7.2.1462-1473
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of High-Yield-Pulp for Hardwood Bleached Kraft Pulp in Paper Production and Its Effect on Alkenyl Succinic Anhydride Sizing

Abstract: In recent years there has been an increasing interest in using high-yield pulp (HYP) as a partial replacement for hardwood bleached kraft pulp (HWBKP) in the production of high-quality fine papers as a cost-effective way of improving the product performance. This study investigated the substitution of HYP for HWBKP and its effect on the Alkenyl Succinic Anhydride (ASA) sizing performance. The results showed that the substitution of an aspen HYP for HWBKP can increase the ASA sizing performance at a HYP substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In addition, the use of alum controls the deposit of hydrolyzed ASA, and the aluminum salt of the hydrolyzed ASA may interact with the anionic charges on cellulose to improve sizing. Furthermore, the application of alum can anchor free hydrolyzed ASA to the fiber as a metal salt to reduce, to delay, or to reverse size reversion due to migration, reorientation or fugitivity [26,52,67,75].…”
Section: • Emulsion Retentionmentioning
confidence: 99%
“…In addition, the use of alum controls the deposit of hydrolyzed ASA, and the aluminum salt of the hydrolyzed ASA may interact with the anionic charges on cellulose to improve sizing. Furthermore, the application of alum can anchor free hydrolyzed ASA to the fiber as a metal salt to reduce, to delay, or to reverse size reversion due to migration, reorientation or fugitivity [26,52,67,75].…”
Section: • Emulsion Retentionmentioning
confidence: 99%
“…For the emulsification, the rotor speed was set to 20,000 rpm, and the shearing time was 2 minutes. The ASA emulsion prepared was uniform and homogeneous (Chen et al 2012), and the freshly prepared ASA emulsion was used in the experiments.…”
Section: Preparation Of the Asa Emulsionsmentioning
confidence: 99%
“…The effects of substituting HYP for hardwood kraft pulp on AKD sizing or rosin sizing have been studied (Hu et al 2004;Li et al 2002a,b;Zhang et al 2007). In a previous study (Chen et al 2012), the substitution of HYP for HWBKP in the production of fine papers and its effect on ASA sizing performance were investigated. Results showed that at a HYP substitution of less than 20%, the ASA sizing efficiency could be increased by using HYP in such a system.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose is to decrease the penetration rate of water or the other fluids into paper. [1][2][3][4] Alkenyl succinic anhydride (ASA), a polar viscous oil, is one of the typical internal sizing agents added to paper furnish as an oil-in-water emulsion. [4][5][6][7] ASA has a relatively high chemical reactivity to both cellulose fibers and water, making it possible to achieve a high sizing performance on paper machine, yet unavoidably undergoing hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…A large quantity of cationic starch has to be employed to improve the sizing performance and to reduce the hydrolysis of ASA in emulsions. [1][2] As a consequence, the obtained ASA emulsions have a fairly low concentration, which results in a rather low production efficiency for the preparation of ASA emulsions. To prepare ASA emulsions with higher ASA content, a co-emulsifier/co-stabilizer is required for reducing the charge amount of starch and suppressing the hydrolysis of ASA.…”
Section: Introductionmentioning
confidence: 99%